Associations of Education With Overall Diet Quality Are Explained by Different Food Groups in Middle-aged and Old Japanese Women - Hashimoto, Ayumi (J Epidemiol, 2021)
BACKGROUND: The disparity of overall diet quality by personal educational attainment has been a public issue. However, it remains unknown which food groups contribute to the disparity. This cross-sectional study assesses which food groups explain associations between education and overall diet quality in Japanese women. METHODS: A total of 3,788 middle-aged (mean age, 47.7 years) and 2,188 older women (mean age, 74.4 years), who lived in 47 prefectures in Japan, provided data on their education (low, middle, and high) and dietary intakes from a diet history questionnaire. A diet quality score (possible score 0–70) was calculated based on seven food components. Mean diet quality scores, with adjustment for lifestyle and neighborhood variables, were estimated by education using a general linear model, and Dunnett’s multiple comparison was conducted. Additionally, mean scores of each food component were estimated by education and compared using the same manner. RESULTS: After adjustment for lifestyle and neighborhood variables, mean diet quality score of high or middle education was higher than low education for both generations. Middle-aged women with high and middle education had higher scores of ‘milk’, ‘snacks, confection, and beverages’, ‘fruits’, and ‘vegetable dishes’ than those with low education. Older women with high and middle education had higher scores of ‘sodium from seasonings’ and ‘fruits’ than those with low education. CONCLUSIONS: This study suggests that positive associations between education and diet quality are explained by different food groups in middle-aged and older Japanese women, which are independent of lifestyle and neighborhood variables.